Temperature aspects of a cuboid crystal in photoacoustic interaction - Sarode, Abhijit P. (Вестник Томского государственного университета. Математика и механика)
When a solid crystal undergoes photoacoustic effect, excitation process occurs due to a fraction of incident radiation absorbed by that sample. The nature of excitation depends on the energy of incident radiation. The relaxation processes, generally non-radiative in nature, are observed. Alternate processes of absorption and non- radiative relaxation cause variation in translational temperature in atoms of the crystal. In this paper, the thermal aspects of an isotropic cuboid crystal of elastic material in photoacoustic interaction are presented. This theoretical determination is carried out by applying the finite Marchi–Fasulo integral transform method within the crystal size limitations of a homogeneous cuboid crystal. The results are obtained in terms of infinite series, and the numerical calculations are carried out by using MATHCAD-7 software. The transient translational temperature on the surface of the cuboid crystal in photoacoustic interaction is mathematically determined in terms of thermal conductivity of the elastic material of the crystal.